HUBUNGAN POLA KONSUMSI MAKANAN TERHADAP KEJADIAN ISPA BALITA - Nursiah, Andi; Idris, Idris; Hafsah, Hafsah; Kistimbar, Siti (Ensiklopedia of Journal, 2025)
Abstract: Acute Respiratory Infection (ARI) is still one of the serious health problems that cause high mortality rates in children worldwide. There are 3 Puskesmas with the highest incidence of ARI, namely Puskesmas Turikale, Puskesmas Moncongloe, and Marusu. Data from Turikale Health Center, ARI disease is included in the 10 highest diseases in 2023, which is 907 cases. The recap report of the ARI control program of Maros Regency, January-November 2023 found 623 cases. The purpose of the study was to determine the relationship between food consumption patterns and the incidence of ARI among children under five. The results showed a relationship between fruit consumption patterns (p value: 0.000) and vegetable consumption patterns (p value: 0.001). It is recommended for health centers to increase counseling related to the dangers of smoking at home, exclusive breastfeeding, and routine consumption of vegetables and fruits in accordance with the Puskesmas work program.Keywords: Toddlers, Fruit, ARI.